Pengaruh Ekstrak Serbuk Kayu Siwak (Salvadora persica) Terhadap Pertumbuhan Bakteri Streptococcus mutans - Mardia Apriansi (University of Prof. Dr. Hazairin, SH, 2017)
The purpose of this study was to determine the effect of wood powder extract Siwak (Salvadora persica) on the growth of Streptococcus mutans bacteria, this study was conducted in May 2015 at the Laboratory of Biology, University of Bengkulu. The method used in this research is Completely Randomized Design (CRD), which consists of 6 treatments and 4 repetitions with the concentration of A: 0%, B: 5%, C: 10%, D: 15%, E: 20%, and F: 20%. The results showed that wood dust siwak extract at a concentration of 5% has been inhibit the growth of bacteria Streptococcus muntans with broad zones of inhibition 85.172 mm2, at a concentration of 10% inhibition zone area 112.304 mm2, at a concentration of 15% inhibition zone area 154.841 mm2 at a concentration of 20% of the total 278.086 mm2 inhibition zone and the concentration of 25% inhibition zone 351.57 mm2 area. Based on the results Analysis Of Variance (ANOVA) is known that wood dust extract siwak with different concentrations of a very significant effect in inhibiting the growth of Streptococcus mutans bacteria. And it can be concluded that the growth of Streptococcus mutans in this study began inhibited at concentrations of 5% so that the minimum inhibitory concentration. Inhibition of Streptococcus mutans bacteria growth is happening at a concentration of up to 25% with broad zones of inhibition that form the most extensive.